Characterization of Various Honey Samples from Different Regions of Morocco Using Physicochemical Parameters, Minerals Content, Antioxidant Properties, and Honey-Specific Protein Pattern - Badiaa Lyoussi; Meryem Bakour; Redouan El-Haskoury; Hamada Imtara; Christophe Hano; Katarína Bíliková (Journal of Food Quality)
Honey is a bee product relatively expensive; therefore, it has been a target of adulteration by many sweeteners. In this work, we evaluated the good quality, authenticity, and content in bioactive molecules of twenty-two Moroccan honey from different botanical origins and geographical areas. For that, the following analyses were determined: the content in total protein and especially the major royal jelly protein (apalbumin 1), the analysis of total acidity, free acidity, lactonic acidity, pH, ash, Pfund, electrical conductivity, and moisture. In addition, the content of sodium, potassium, calcium, and magnesium, the dosage of polyphenols, flavones, and flavonols, and the antioxidant activities were assessed. All analyzed samples had good antioxidant activities and present a source of antioxidant compounds, the predominant mineral in all honey samples was potassium, and the physicochemical parameters are in line with the standards’ recommended limits. The content of honey samples in total protein and apalbumin 1 ranged between 212 μg/g and 4121.2 μg/g and between 27.4 μg/g and 790.82 μg/g, respectively. Overall, the detection of apalbumin 1 in all honey samples and the results of physicochemical parameters, minerals, bioactive compounds, and antioxidant activities confirm the authenticity and no adulteration of Moroccan honey.